Study of novel anticancer 4-thiazolidinone derivatives. (25th January 2017) - Szychowski, Konrad A.; Leja, Marcin L.; Kaminskyy, Danylo V.; Binduga, Urszula E.; Pinyazhko, Oleh R.; Lesyk, Roman B.; Gmiński, Jan
Abstract: 4-Thiazolidinones are a known class of prospective drug-like molecules, especially in the design of new anticancer agents. Two of the most prominent subtypes of these compounds are 5-ene-2-amino(amino)-4-thiazolidinones and thiopyrano[2, 3- d ]thiazoles. The latter are considered to be cyclic mimetics of biologically active 5-ene-4-thiazolidinones with similar pharmacological profiles. Therefore, the aim of this study was to evaluate the impact of 4-thiazolidinone-based compounds on cytotoxicity, the apoptotic process, and metabolism in the human squamous carcinoma (SCC-15) cell line. The SCC-15 cells were cultured in phenol red-free DMEM/F12 medium supplemented with 10% FBS, hydrocortisone, and exposed to rising concentrations (1 nM–100 μM) of the studied compounds for 6, 24 and 48 h. Afterwards, reactive oxygen species (ROS) formation, cell viability, caspase-3 activity, and cell metabolism were measured. The obtained results showed that all of the studied compounds in a wide range of concentrations (1 nM–100 μM) increased DCF fluorescence which suggests a stimulation of ROS production. Nevertheless, these new compounds showed cytotoxic and proapoptotic properties only at high (10–100 μM) concentrations. Our studies are the first to be carried out on these compounds and require further investigation to clarify the mechanism of action of their anticancer potential. Graphical abstract: Highlights: Les-2194, Les-3377, and Les-3640 increased DCF fluorescence in SCC-15 cells. The high μM concentrations of Les-2194, Les-3377, and Les-3640 have cytotoxic properties. Les-2194, Les-3377, and Les-3640 showed proapoptotic properties in the high μM concentrations.